Laju Korosi Baja Karbon Rendah Besi ASTM A36 dan Paku pada Lingkungan Perairan Manyar Gresik - Sonny Bambang Dianna; Vita Ambarwati; Lisa Puspita Ariyanto (SURYA TEKNIKA, 2025)
This study aims to analyze the corrosion rate of low carbon steel in the coastal environment of Manyar District, Gresik Regency, by comparing the effects of seawater and river estuary water as well as deformation through different bending angles (45° and 90°). The weight loss method was used, with specimen immersion conducted for one month. The results showed that seawater, due to its high salinity, caused a significantly higher corrosion rate compared to estuary water. Low carbon steel specimens (M) were more susceptible to corrosion than nail specimens (P), likely due to differences in material composition and surface treatment. Additionally, deformation increased the corrosion rate due to stress concentration and micro-pooling at bent areas. This study offers a quantitative overview of steel degradation under real-world conditions and recommends additional protective measures, such as coatings or stress-minimizing designs. Further research is encouraged, including microscopic analysis and numerical simulations for more accurate prediction of material lifespan.